Yagonia Roberts (Brachiopoda: Chonetidina) from the Malimán Formation, Lower Carboniferous of western Argentina: Palaeobiogeographical implications - Taboada, Arturo Cesar (2009)
A new anoplid chonetid species, Yagonia furquei sp. nov., is described from the Lower Carboniferous (late Tournaisian-early Visean) Maliman Formation of western Argentina. The associated temperate 'Malimanian' fauna is suggested to indicate an initial biotic segregation that took place in western Gondwana (southwestern South America), a palaeobiogeographic event that predated the late Visean global cooling and associated major palaeolatitudinal biotic differentiation. Occurrences of Yagonia are here interpreted as evidence of a 'south to north' faunal migration pathway, here named the Austropanthalassic-Rheic oceanic corridor, established in western Gondwana during the late Early Carboniferous.